Limited dispersal and geographic barriers cause population differentiation and structuring in Begonia maxwelliana at both large and small scales - Chan, Yoke Mui; Tnah, Lee Hong; Lee, Soon Leong; Bhassu, Subha; Lee, Chai Ting; Chua, Lillian Swee Lian (Taylor & Francis, 2018)
Background: Genetic divergence is one of the key processes in speciation. In the Begoniaceae, genetic divergence caused by limited gene flow may explain its high species diversity and endemicity. This hypothesis has been supported by past genetic work but there is a lack of empirical studies on the causes of limited gene flow. Aim: To identify the causes of limited gene flow in Begonia. Methods: We examined the genetic structure among the populations of Begonia maxwelliana at the macro-and micro-spatial scales using microsatellites, measured seed dispersal range and observed flowering phenology. Results: Population differentiation and structuring were detected at both the macro-and micro-scales. Dispersal range was short, and all populations showed similar reproductive behaviour. Conclusions: The strong population differentiation and structuring among the populations studied imply that they are evolutionarily significant units and possible candidates for speciation. Geographical barriers and limited seed dispersal restrict gene flow in the populations, and these factors may be responsible for the rapid speciation and large diversity in the family.